Exploiting Externalities to Estimate the Long-Term Effects of Early Childhood Deworming - Ozier, Owen (World Bank Group, Washington, DC, 2014)
This paper investigates whether a large-scale deworming intervention aimed at primary school pupils in western Kenya had long-term effects on young children in the region. The paper exploits positive externalities from the program to estimate the impact on younger children who did not receive treatment directly. Ten years after the intervention, large cognitive effects are found -- comparable to between 0.5 and 0.8 years of schooling -- for children who were less than one year old when their communities received mass deworming treatment. Because mass deworming was administered through schools, effects are estimated among children who were likely to have older siblings in schools receiving the treatment directly; in this subpopulation, effects are nearly twice as large.